You Win Some, You Lose Some: Pension Reform in Bachelet's First and Second Administrations. Issue 2 (August 2019) - Borzutzky, Silvia
This article analyses and compares President Bachelet's successful efforts to reform the Chilean pension system in 2008 and her failure to achieve the same objective in 2017. The article addresses the impact of electoral promises, policy legacies, policy ideology, presidential power, the role of the private sector, and the role that the government coalitions had in the process of pension reform during the Bachelet administrations. We argue that the 2008 reform was possible because of Bachelet's personal commitment to reform and the presence of a stable governing coalition that had the will and capacity to legislate. In the second administration, although the policy legacies and ideology had remained the same, the reform did not materialise due to intense conflict within the administration and within the government coalition, as well as conflict between the administration and the coalition. These conflicts, in turn, generated a vicious cycle responsible for Bachelet's declining popularity, limited political capital, and reduced support for reform. A stagnant economy further undermined these efforts. In brief, this article argues that when assessing success and failure in pension policy reform it is important to analyse not only policy legacies and political ideology but also the strength of the executive, the cohesion of the governing coalition, and the country's economic performance.